A checklist of flowering plants of Panchase Protected Forest, Kaski district, central Nepal - Bhandari, Prabin; Budhamagar, Shanta; Shrestha, Krishna K. (Journal of Natural History Museum, 2018)
Panchase Protected Forest (PPF), situated at the junction of three districts Kaski, Syangjaand Parbat with an elevation range of 900-2517m representing mid hills of Nepal. This study was carried out with an aim of documenting the flowering plant diversity of the Panchase Protected Forest, Kaski district, comprising three VDCs, Bhadaure Tamage, Chapakot and Pumdi Bhumdi. General survey, covering all seasons was organized (from June 2014 to May2015) for collecting the plant species. Published literatures and herbarium specimens were also consulted for documenting the species. Identification of the collected specimens was made through consulting relevant literatures, herbarium specimens and expert consultation. A total of 613 species belonging to 393 genera and 111 families have been documented from this area. The dominant family was Orchidaceae (49 genera and 125 species) followed by Poaceae (25 spp.), Asteraceae (25 spp.) and others. Six endemic plants, Begonia flagellaris (Begoniaceae), Eria pokharensis, Gastrochilus nepalensis, Oberonia nepalensis, Odontochilusnandae and Panisea panchaseensis (Orchidaceae) were also reported. Similarly, presentresearch revealed two taxa as new record for flora of Nepal, Dischidia bengalensis Colebr. (Apocynaceae) and Phreatia elegans Lindl. (Orchidaceae). The present findings suggest that PPF is one of the hotspot for floral diversity representing mid hills of Nepal and this pristine habitat for orchid should be developed as ‘Orchid Sanctuary’.